Corruzione pubblica Repressione penale e prevenzione amministrativa - PALAZZO, FRANCESCO CARLO (Atti, 2011)
This book contains the proceedings of the seminar held in Florence on 6 May 2011 within the framework of a research project of national scope funded by the Ministry of Education (MUIR). The principal inspiring aim is the quest for synergy between criminal law and administrative law in the activities aimed at fighting corruption. The 'final' interests damaged by corruption are fundamental (public safety, national economy), such as to demand the stigmatisation and efficacy inherent to the penal instrument. However, no less important is the prevention aspect recommended by the European and international institutions, which can be achieved through a real and effective reinforcement of administrative instruments, such as the prevention of conflicts of interest or the strengthening of the disciplinary system.